Islam in America by Mahmoud Yousef Shawarbi: Introduced and Translated by Maytha Alhassen. (2nd October 2015) - Alhassen, Maytha
Abstract : The article offers an insight into the meanings of American blackness within Arab Muslim and Arabic imaginaries in the mid to late 20 th century when the linkages between global post-colonial nationalist and liberation struggles signaled revolutionary possibility in the US and the Middle East. Through the Arabic- to -English translation of Egyptian Fulbright scholar and transnational Muslim figure Mahmoud Youssef Shawarbi's informal ethnography on the Nation of Islam, a chapter in a report for organization Dissemination of Islamic Culture on Islam in America, we begin to see the contours of an Arab and Arabic imaginary around Black Americans and Islam in America as it intersects with American Blackness. What emerges in this chapter titled 'Al Amreekan as-Simmr wa al-Gameeyah al-Islamiyyah bee Sheekago' [Black Americans and the Islamic Organization of Chicago] is the surprisingly consistent use of the term simmr, the plural of asmar to as a signifier of American Blackness. Often translated as a 'dark-complexioned person', asmar is a feature in Arabic cultural productions as a term of endearment to describe a beloved, a frequent central character in Arabic love songs. At first blush, asmar can be read as a marker of extended kinship, but that kinship is rapidly compromised/complicated by Shawarbi's reproduction of Arab supremacist and paternalistic scripts, seeking to 'correct' the Nation to 'right Islamic belief', on Black American Islam. The article starts with a contextual analysis 'Black Americans and the Islamic Organization of Chicago', followed by a translation of the chapter from Arabic to English.